Off and Running? Technology, Trade and the Rising Demand for Skilled Workers in Latin America - Sanchez-Paramo, Carolina; Schady, Norbert (World Bank, Washington, DC, 2014)
The authors describe the evolution of relative wages in five Latin American countries-Argentina, Brazil, Chile, Colombia, and Mexico. They use repeated cross-sections of household surveys, and decompose the evolution of relative wages into factors associated with changes in relative supply and relative demand. The authors have three main conclusions: 1) Increases in the relative wages of the most skilled (university-educated) workers took place concurrently with increases in their relative abundance in all of the countries except Brazil. This is strong evidence of increases in the demand for skilled workers. 2) Increases in the wage bill of skilled workers occurred largely within sectors, and in the same sectors in different countries, which is consistent with skill-biased technological change. 3) Trade appears to be an important transmission mechanism. Increases in the demand for the most skilled workers took place at a time when countries in Latin America considerably increased the penetration of imports, including imports of capital goods. The authors show that changes in the volume and research and development intensity of imports are significantly related to changes in the demand for more skilled workers in Latin America. Their research complements earlier work on the effects of technology transmitted through trade on productivity and on the demand for skilled labor.